Diagnostic accuracy of fetal growth charts for placenta-related fetal growth restriction. (February 2021) - Melamed, Nir; Hiersch, Liran; Aviram, Amir; Mei-Dan, Elad; Keating, Sarah; Kingdom, John C.
Abstract: Introduction: The choice of fetal growth chart to be used in antenatal screening for fetal growth restriction (FGR) has an important impact on the proportion of fetuses diagnosed as small for gestational age (SGA), and on the detection rate for FGR. We aimed to compare diagnostic accuracy of SGA diagnosed using four different common fetal growth charts [Hadlock, Intergrowth-21st (IG21), World Health Organization (WHO), and National Institute of Child Health and Human Development (NICHD)], for abnormal placental pathology. Methods: A secondary analysis of data from a prospective cohort study in low-risk nulliparous women. The exposure was SGA (birthweight <10th centile for gestational age) using each of the four charts. The outcomes were one of three types of abnormal placental pathology associated with fetal growth restriction: maternal vascular malperfusion (MVM), chronic villitis, and fetal vascular malperfusion. Results: A total of 742 nulliparous women met the study criteria. The proportion of SGA was closest to the expected rate of 10% using the Hadlock chart (12.7%). The detection rates (DR) and false positive rates (FPR) for MVM pathology were similar for the Hadlock (DR = 53.1%, FPR = 10.8%), WHO (DR = 59.4%, FPR = 14.2%), and NICHD (DR = 53.1%, FPR = 12.3%) charts, and each was superior when compared to the IG21 chart (DR = 34.4%, FPR = 3.8%, p < 0.001). The diagnosis of SGA was associated with increased risks of preeclampsia and preterm birth for all four charts. Discussion: The selection of fetal growth chart to be used in screening programs for FGR has important implications with regard to the false positive and detection rate for FGR. Highlights: The proportion of SGA detected by the Hadlock chart was closest to the expected 10%. The detection rates of the Hadlock, WHO, and NICHD charts for MVM was similar. The detection rate for MVM of the IG21 chart was lower than the other charts.